O princípio da isonomia e as imunidades tributárias: um cotejo entre a Funpresp e os fundos de pensão privados - Hissa, Carolina Simão Odisio (2018)
The present paper undertakes an analysis of the principle of isonomy in relation to the tax treatment provided to the Federal Public Servants' Supplementary Pension Foundation - Funpresp and to the private pension funds. Preliminarily, it traces the historical evolution of Social Security in Brazil, as well as the influence of the consolidation of the Social Welfare State in the realization of fundamental social rights, including complementary pension. This, in turn, is understood as the most recent significant change in the civil service pension scheme, which culminated in the creation of a closed private pension entity of a public nature and private legal personality to administer and execute the pension plans of the federal public servants. The legal nature attributed to Funpresp generates a mismatch in relation to private pension funds, insofar as their public character may lead to the incidence of reciprocal immunity, when private foundations of supplementary pensions are not presumed to have a similar immune standard, identical regulatory activities.